EVALUASI KURIKULUM TINGKAT SATUAN PENDIDIKAN PADA SEKOLAH DASAR NEGERI 67 KOTA BANDA ACEH - Yusnaini .; Nasir Usman; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: Evaluation of curriculum is important to know the achievements of the program implemented, implementation, monitoring and supporting the implementation of SBC factors. This study aimed to describe the data on the evaluation of the implementation of curriculum in 67 public primary schools in Banda Aceh. This research uses descriptive qualitative method. Data was collected through interviews, observation and documentation as well as filling a questionnaire study. Data analysis techniques such as data reduction, data display and conclusion. Subjects in this study were principals, vice-principals, and teachers. the conclusion is: (1) Content Document 1 curriculum according to the guidelines but still lacking an explanation of life skills education, education-based local and global. Syllabus and RPP was adopted from examples issued by the National Education Standards, but most of the teachers have been adapted according to the conditions of the school. Syllabus and RPP are still weak in terms of withdrawal indicators and assessment as well as low-grade lesson plan is not thematic. (2) Implementation of SBC Document 1 is in accordance with the plan, but in self-development activities there is little difference for not conducting counseling. Implementation has not been fully based learning lesson plans. Low-grade teacher is not using a thematic approach. Teachers in core activities already conducting exploration activities, elaboration and confirmation as well as carry out the grip so that the students active and creative, but there is still a small proportion of teachers who have not been able to do well. Teachers already use a variety of media and learning resources, but there is still a small fraction of teachers who have not used it. Teachers at the preliminary event does not convey the purpose, benefits, coverage of materials and learning strategies, and the cover does not carry out the activities of reflection. Teachers in implementing learning assessment still shortcomings, such as is found to be less variability assessment technique, lack of due indicators to the basic competencies and the assessment techniques used and the results of the assessment has not been used as a follow-up plan. (3) Supervisors and principals have oversight of curriculum through supervision activities are done once a year. (4) The availability of a complete infrastructure, support parents, and principals, high student motivation, and cooperation among teachers is supportive of curriculum implementation and the weak ability of teachers in planning thematic lesson plans, thematic application and design instructional materials and assessment , is a barrier in the application of the SBC.Keywords: Evaluation, Implementation, Curriculum Education UnitAbstrak: Evaluasi KTSP penting dilaksanakan untuk mengetahui capaian program, pelaksanaan, pengawasan dan faktor pendukung penerapan KTSP. Penelitian ini bertujuan untuk mendeskripsikan data tentang evaluasi penerapan KTSP pada SD Negeri 67 Kota Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif metode deskriptif. Teknik pengumpulan data dilakukan melalui wawancara, observasi dan studi dokumentasi. Teknik analisis data berupa reduksi data, penyajian data, dan kesimpulan. Subjek dalam penelitian ini adalah kepala sekolah, wakil kepala sekolah, dan guru. kesimpulannya adalah: (1) Isi Dokumen 1 KTSP sesuai panduan namun masih kurang penjelasan tentang pendidikan kecakapan hidup, pendidikan berbasis lokal dan global. Silabus dan RPP diadopsi dari contoh yang dikeluarkan oleh BSNP, namun sebagian besar guru sudah mengadaptasi sesuai dengan kondisi sekolahnya. Silabus dan RPP masih lemah dalam hal penarikan indikator dan penilaian sertaRPP kelas rendah belum tematik. (2) Pelaksanaan KTSP Dokumen 1 sudah sesuai dengan perencanaan. Pelaksanaan pembelajaran belum sepenuhnya berdasarkan RPP. Guru kelas rendah belum menggunakan pendekatan tematik. Guru pada kegiatan inti sudah melaksanakan kegiatan eksplorasi, elaborasi dan konfirmasi serta melaksanakan pakem sehingga siswa aktif dan kreatif namun masih ada sebagian kecil guru yang belum dapat melakukannya dengan baik. Guru sudah menggunakan berbagai media dan sumber belajar, namun masih ada sebagian kecil guru yang belum menggunakannya. Guru pada kegiatan pendahuluan tidak menyampaikan tujuan, manfaat, cakupan materi dan strategi belajar, dan pada kegiatan penutup tidak melaksanakan refleksi. Guru dalam melaksanakan penilaian pembelajaran masih terdapat kelemahan-kelemahan, seperti masih ditemukan kurang bervariasinya tehnik penilaian, kurang sesuainya indikator dengan kompetensi dasar dan dengan tehnik penilaian yang digunakan serta hasil penilaian belum dimanfaatkan sebagai bahan menyusun rencana tindak lanjut. (3) Pengawas dan kepala sekolah telah melakukan pengawasan KTSP melalui kegiatan supervisi yang dilakukan setahun sekali. (4) Tersedianya sarana prasarana yang lengkap, dukungan orang tua, dan kepala sekolah, motivasi siswa yang tinggi, serta kerjasama antar guru menjadi faktor pendukung penerapan KTSP dan masih lemahnya kemampuan guru dalam hal perencanaan RPP tematik, penerapan tematik dan perancangan bahan ajar serta penilaian, menjadi faktor penghambat penerapan KTSP.Kata Kunci: Evaluasi, Implementasi, Kurikulum Satuan Pendidikan